A case study of the carbon footprint of milk from high-performing confinement and grass-based dairy farms - O'Brien, D.; Capper, J.L.; Garnsworthy, P.C.; Grainger, C.; Shalloo, L. (American Dairy Science Association, 2014)
Life cycle assessment (LCA) is the preferred methodology to assess carbon footprint per unit of milk. The objective of this case study was to apply a LCA method to compare carbon footprints of high performance confinement and grass-based dairy farms. Physical performance data from research herds were used to quantify carbon footprints of a high performance Irish grass-based dairy system and a top performing UK confinement dairy system. For the USA confinement dairy system, data from the top 5% of herds of a national database were used. Life cycle assessment was applied using the same dairy farm greenhouse gas (GHG) model for all dairy systems. The model estimated all on and off-farm GHG sources associated with dairy production until milk is sold from the farm in kg of carbon dioxide equivalents (CO2-eq) and allocated emissions between milk and meat. The carbon footprint of milk was calculated by expressing the GHG emissions attributed to milk per t of energy corrected milk (ECM). The comparison showed when GHG emissions were only attributed to milk, the carbon footprint of milk from the IRE grass-based system (837 kg of CO2-eq/t of ECM)¬ was 5% lower than the UK confinement system (877 kg of CO2-eq/t of ECM) and 7% lower than the USA confinement system (898 kg of CO2-eq/t of ECM). However, without grassland carbon sequestration, the grass-based and confinement dairy systems had similar carbon footprints per t of ECM. Emission algorithms and allocation of GHG emissions between milk and meat also affected the relative difference and order of dairy system carbon footprints. For instance, depending on the method chosen to allocate emissions between milk and meat, the relative difference between the carbon footprints of grass-based and confinement dairy systems varied by 2-22%. This indicates that further harmonization of several aspects of the LCA methodology is required to compare carbon footprints of contrasting dairy systems. In comparison to recent reports that assess the carbon footprint of milk from average Irish, UK and USA dairy systems, this case study indicates that top performing herds of the respective nations have carbon footprints 27-32% lower than average dairy systems. Although, differences between studies are partly explained by methodological inconsistency, the comparison suggests that there is potential to reduce the carbon footprint of milk in each of the nations by implementing practices that improve productivity.